Recognition of Child Placement Periods in LPKS as Part of Detention: Regulatory Disharmony and the Need for Legal Reconstruction - Anggi Amelia Putri; Rosa Tedjabuana (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
Ideally, every form of deprivation of liberty for children in conflict with the law, whether through detention in LPAS or placement in LPKS, should receive equal recognition within the framework of criminal procedure law. This principle aligns with the doctrine of the best interest of the child, which requires fair and consistent treatment standards across Indonesia. However, practice shows a lack of uniformity. Some law enforcement officers recognize placement in LPKS as part of detention, while others do not, due to the absence of explicit provisions in Law No. 11 of 2012 on the Juvenile Criminal Justice System (SPPA). This situation creates legal uncertainty and double harm for children, both juridically and psychologically. This study aims to analyze the urgency of recognizing the period of placement in LPKS as part of detention by highlighting the disharmony between regulations and practice, while also offering regulatory reconstruction to ensure legal certainty. The methodology employed is library research with a qualitative approach, using a normative legal study with a descriptive-analytical method. The findings reveal a legal vacuum concerning the status of placement in LPKS, which has led to disharmony in various regions. Regulatory reconstruction is therefore necessary so that the placement period is recognized as part of detention, thereby ensuring the protection of children’s rights, guaranteeing legal certainty, and fulfilling the primary objectives of the SPPA, namely rehabilitation and child protection.